2000
DOI: 10.1097/00003226-200007000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Levels of Collagen Degradation Products (Telopeptides) in the Tear Film of Patients with Keratoconus

Abstract: The tear film of patients with keratoconus contains higher levels of telopeptides than those of control subjects. Determination of telopeptide levels in tears could be useful for the follow-up of keratoconus development in patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 17 publications
2
20
0
1
Order By: Relevance
“…[129][130][131] One study found higher concentrations of C-terminal telopeptide (type I collagen degradation products) in tears of patients with keratoconus than in controls. 132 This behavior is due to the increase of activity and number of enzymes that remodel the ECM; the most prominent changes in keratoconic cornea were observed in collagenase MMP-13, and in particular, in cathepsin K and human trypsin-2, which were strongly expressed in keratoconus, suggesting a role in intra-and extracellular pathological collagen destruction, respectively. 23 A similar report documented 1.9 times more proteolytic activity and gelatinases/collagenases expression (MMP-1, MMP-3, MMP-7, and MMP-13, as well as IL-4, IL-6, and TNF-α that increase the production and activity of the former).…”
Section: Enzymatic Imbalancementioning
confidence: 99%
“…[129][130][131] One study found higher concentrations of C-terminal telopeptide (type I collagen degradation products) in tears of patients with keratoconus than in controls. 132 This behavior is due to the increase of activity and number of enzymes that remodel the ECM; the most prominent changes in keratoconic cornea were observed in collagenase MMP-13, and in particular, in cathepsin K and human trypsin-2, which were strongly expressed in keratoconus, suggesting a role in intra-and extracellular pathological collagen destruction, respectively. 23 A similar report documented 1.9 times more proteolytic activity and gelatinases/collagenases expression (MMP-1, MMP-3, MMP-7, and MMP-13, as well as IL-4, IL-6, and TNF-α that increase the production and activity of the former).…”
Section: Enzymatic Imbalancementioning
confidence: 99%
“…Factors determining or affecting the progression or stabilization of KC have not been well understood [3,4]. During tissue degradation - a hallmark of the disease - the expression of inflammatory mediators such as proinflammatory cytokines, cell adhesion molecules and matrix metalloproteinases (MMPs), as well as other enzymes and growth factors, has also been described [4,5,6,7,8,9,10,11,12,13]. Recent studies have suggested a role of the inflammatory events in the pathogenesis of KC [4,14].…”
Section: Introductionmentioning
confidence: 99%
“…The corneal thinning in KC seems to result from a loss of structural components such as collagen. This loss results more from increased proteolytic activity than from decreased synthesis of these elements [1,26]. Especially the membrane-type 1 matrix metalloprotease and matrix metalloprotease 2 are upregulated in KC [4].…”
Section: Discussionmentioning
confidence: 99%